Blacklight sintering of ceramics. Issue 6 (22nd April 2022) - Porz, Lukas; Scherer, Michael; Huhn, Daniel; Heine, Luisa-Marie; Britten, Simon; Rebohle, Lars; Neubert, Marcel; Brown, Martin; Lascelles, Peter; Kitson, Ross; Rettenwander, Daniel; Fulanovic, Lovro; et al.
Abstract : Illumination with photon energy above the band gap enables super-fast sintering of ceramics on-the-spot. This scalable container- and contactless process opens new design options and boosts flexibility while offering outstanding energy efficiency. Abstract : For millennia, ceramics have been densified via sintering in a furnace, a time-consuming and energy-intensive process. The need to minimize environmental impact calls for new physical concepts beyond large kilns relying on thermal radiation and insulation. Here, we realize ultrarapid heating with intense blue and UV-light. Thermal management is quantified in experiment and finite element modelling and features a balance between absorbed and radiated energy. With photon energy above the band gap to optimize absorption, bulk ceramics are sintered within seconds and with outstanding efficiency (≈2 kWh kg −1 ) independent of batch size. Sintering on-the-spot with blacklight as a versatile and widely applicable power source is demonstrated on ceramics needed for energy storage and conversion and in electronic and structural applications foreshadowing economic scalability.